1990
DOI: 10.1007/bf02544325
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in rat tissue slices: Effect of dietary vitamin E, corn oil‐lard and menhaden oil

Abstract: Rats were fed for 5 weeks either 10% (w/w) menhaden oil (MO) or a 10% corn oil-lard (COL) mixture (1:1) in diets with less than or equal to 5 IU or less than or equal to 2 IU/kg vitamin E, respectively, or the same diets supplemented with d-alpha-tocopheryl succinate to a total of 35 and 180 IU vitamin E/kg, respectively. Slices of liver and heart from these rats were used to study lipid peroxidation in vitro. Thiobarbituric acid-reactive substances (TBARS) were measured in the medium after incubation of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 22 publications
7
35
0
1
Order By: Relevance
“…By eating fish or fish oils we load our phospholipids with EPA and DHA at the expense of their content of arachidonic acid, increasing the susceptibility of lipid membranes to oxidative damage. This effect has been observed in experimental animals by several authors (Mails et al 1990, Garrido et al 1989, Leibovitz et al 1990). Moreover, age appears as an important factor in the development of these susceptibility.…”
Section: Technological Approaches To Extract and Preserve Omega-3 Fatsupporting
confidence: 58%
“…By eating fish or fish oils we load our phospholipids with EPA and DHA at the expense of their content of arachidonic acid, increasing the susceptibility of lipid membranes to oxidative damage. This effect has been observed in experimental animals by several authors (Mails et al 1990, Garrido et al 1989, Leibovitz et al 1990). Moreover, age appears as an important factor in the development of these susceptibility.…”
Section: Technological Approaches To Extract and Preserve Omega-3 Fatsupporting
confidence: 58%
“…PUFAs, which are not protected from oxidation, may promote lipid peroxidation and degradation of cellular membranes, which can lead to an excessive inflow of Ca into the cell. In the discussed experiment, vitamin E was supplied in considerable amounts, therefore we may suppose that the obtained results were only a consequence of PUFA n-3 activity (Leibovitz et al, 1990) and not of their oxidized derivatives.…”
Section: Resultsmentioning
confidence: 90%
“…These results were in agreement with the finding reported by JOHNSON et al [17], who proved that the use of different doses of BHA mixed with lard for six weeks, had no effect on PUFA composition of rats liver. Also, LEIBOVITZ et al [20], revealed that different doses of vitamin E in groups of rats fed the same lipid did not affect the fatty acids of liver composition.…”
Section: Resultsmentioning
confidence: 96%